Obtaining a complex of 1-vinyl-1,2,4-triazole with gold chloride and study of its thermal and biological properties - A. H. Hasratyan (ՀՀ ԳԱԱ հրատ.)
The complex (CVT) of 1-vinyl-1,2,4-triazole (VT) with HAuCl4 was synthesized, its physicochemical characteristics were determined. It has been shown that the formation of the complex occurs through the triazole nitrogen atom N4. Using the results of thermogravimetric and elemental analyses, it has been found that regardless of the molar ratio of the starting components (VT: HAuCl4 - 1:1; 1:2; 2:1), a complex of 1:1 composition is formed. The effect of compounds VT, HAuCl4, and CVT on postganglionic sympathetic nerve fibers and adrenergic receptors was studied. It has been found that the tested compounds have a weak sympatholytic and adrenomimetic effect. Սինթեզվել է 1-վինիլ-1,2,4-տրիազոլի (ՎՏ) կոմպլեքսը HAuCl4–ի (ԿՎՏ) հետ, որոշվել են նրա ֆիզիկոքիմիական հատկությունները: Ցույց է տրվել, որ կոմպլեքսի առաջացումը տեղի է ունենում տրիազոլային օղակում N4 ազոտի ատոմի միջոցով: Թերմոգրավիմետրիկ և էլեմենտ անալիզների օգնությամբ պարզվել է, որ անկախ ելանյութերի մոլային հարաբերակցությունից (ՎՏ: HAuCl4 – 1:1, 1:2, 2:1) առաջանում է 1:1 բաղադրությամբ կոմպլեքսը: Ուսումնասիրվել է ՎՏ, HAuCl4 և ԿՎՏ միացությունների ազդեցությունը հետգանգլիոնային սիմպաթիկ նյարդային մանրաթելերի և ադրենոռեցեպտորների վրա: Հայտնաբերվել է, որ փորձարկված միացություններն ունեն թույլ սիմպաթոլիտիկ և ադրենոմիմետիկ ազդեցություն: Синтезирован комплекс (КВТ) 1-винил-1,2,4-триазола (ВТ) с HAuCl4, определены его физико-химические характеристики. Показано, что образование комплекса происходит через триазольный атом азота N4. При помощи результатов термогравиметрического и элементного анализов установлено, что независимо от мольного соотношения исходных компонентов (ВТ: HAuCl4 – 1:1, 1:2, 2:1) образуется комплекс состава 1:1. Исследовано действие соединений ВТ, HAuCl4 и КВТ на постганглионарные симпатические нервные волокна и адренорецепторы. Установлено, что испытуемые соединения обладают слабым симпатолитическим и адреномиметическим действием.
Keywords: Organic Chemistry